Weight illusion by presenting vibration to the fingertip - Kim, Giryeon; Okamoto, Shogo; Akiyama, Yasuhiro; Yamada, Youji (Frontiers in Virtual Reality, 2022)
It is difficult for humans to perceive weight accurately, because the perception of weight is produced by the process of multisensory integration. This implies that, by manipulating certain factors, the weight of an object could be perceived differently from the actual weight. Here, the effects of vibration on weight perception were investigated using behavioral tests and questionnaires. As a behavioral test, from a number of identically appearing non-vibrating boxes of different weights, participants had to select a box that they perceived to be of the same weight as a vibrating box. They were also asked whether vibration affected the perceived weight of the box. Even though they reported that vibration created an illusion of weight, the results of the behavioral test did not show a statistically significant effect of vibration on perceived weight. Furthermore, we investigated how the frequency of vibration affected the illusion and found that the weight illusion requires smaller acceleration of vibration at lower frequencies, such as 30 Hz. The illusion was more intense at lower frequencies than at higher frequencies, such as 200 and 300 Hz. Thus, this study demonstrated that vibrotactile stimuli presented to the fingertips produce a weight illusion: vibrating objects are perceived to feel heavier. Even though the principles of this illusion are still unknown, the effect is concrete, and our approach allows easy implementation in virtual reality applications.